Does social capital play a role in TH model of university-industry cooperation: an evidence of the Croatian experience - Švarc, Jadranka; Perković, Juraj; Lažnjak, Jasminka (2009)
The paper presents the results of the first empirical research with the attempts to analyse and understand the influence of social capital on the implementation of the TH III model and performance of innovation policy in Croatia. The TH III model is understood as an analytical tool and theoretical basis for the implementation of the modern innovation policy which tries to foster the interactions between the three helices of university- industry-government cooperation. It follows growing tendencies to connect the concept of the national innovation system with the concept of social capital as invisible social “ glue” which helps economic behaviour and economic growth. The analysis is based on questionnaire- based survey conducted in 2007 targeted at the project leaders who have taken part in one of the first innovation policy programme in Croatia (TEST) aimed at fostering science-industry cooperation and commercialization of research results of the public research sector. The main findings of the research indicate that deficiencies of social capital such as low trust in government institutions or value orientations which disfavour communication between the three helices of TH III model prevent the socio-cultural change needed for stronger science-industry cooperation and reduce the level of performance of innovation policy.
Projekt MZOS
Projekt MZOS
ENG